TRANSFORMATIONAL LEADERSHIP IN MALUKU'S DISADVANTAGED, FRONTIER, AND OUTERMOST SCHOOLS: A BURU MULTI-SITE STUDY - Kartika Eka Prasetiyani; Patrisius Rahabav; Paul Arjanto (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Principal leadership is crucial for sustaining school quality in Indonesia's disadvantaged, frontier, and outermost (3T) areas, where limited infrastructure, teacher shortages, and difficult access often constrain educational services. This study aims to analyze the implementation of transformational leadership by principals at SMP Negeri 28 Buru and SMP Negeri 37 Buru, Maluku Province; identify its impacts on school performance; and explain supporting and inhibiting factors. A qualitative multi-site design was applied. Data were collected through in-depth interviews with principals, teachers, and students, direct observation of school activities, and documentation of school programs and student achievements. The data were analyzed using data reduction, data display, conclusion drawing, and cross-site comparison, while credibility was strengthened through source triangulation, method triangulation, and member checking. The findings show that both principals applied the four dimensions of transformational leadership. Idealized influence appeared in discipline, integrity, and direct involvement in school activities. Inspirational motivation was reflected in efforts to build optimism and a shared vision. Intellectual stimulation encouraged teachers to use simple learning media and local resources. Individualized consideration appeared in personal coaching, emotional support, and attention to student potential. These practices improved teacher discipline, work motivation, student confidence, learning creativity, and community participation. Supporting factors included teacher solidarity, principal commitment, community support, operational assistance, and students' learning motivation, whereas obstacles included insufficient facilities, difficult geography, teacher shortages, limited professional training, and weak technology access.